Influence of Elevation on Slake Durability Index of Quartz Mica Schist: A Case Study of East Slope of Manjiazhai Open Pit. (12th January 2022) - Lu, Yongfeng; Hou, Kepeng; Sun, Huafen; Sun, Wei; Zhang, Shengyou; Jiang, Jun
Abstract : In order to study the influence of elevation on the slake durability index of the quartz mica schist, the quartz mica schist with different elevations on the east slope of the Manjiazhai open-pit mine is taken as the research object, and based on laboratory tests and statistical analysis, the variation of negative correlation between the slake durability index and elevation is obtained. The disintegration mechanism of quartz mica schist at different elevations is also discussed. The test results show that the disintegration characteristics of quartz mica schist at different elevations are related to its mineral composition, fissure channel size, and rock damage effect. As the slope height increases, the ratio of mica to quartz in the rock increases, and the greater the porosity of the rock, the more fissures in the rock, the greater the permeability coefficient, and the more obvious the change of effective stress of rock under osmotic pressure. At the same time, the higher the slope elevation of open-pit mine, the longer the weathering time of rock, the higher the cumulative damage of rock, and the lower the rock slake durability index. This study provides a new idea for guiding the research on the disintegration characteristics of similar soft rock slopes in the elevation direction.